Seropositivity to Cytomegalovirus, Inflammation, All-Cause and Cardiovascular Disease-Related Mortality in the United States - Simanek, Amanda M.; Dowd, Jennifer Beam; Pawelec, Graham; Melzer, David; Dutta, Ambarish; Aiello, Allison E. (PLOS ONE, 2011)
Background Studies have suggested that CMV infection may influence cardiovascular disease (CVD) risk and mortality. However, there have been no large-scale examinations of these relationships among demographically diverse populations. The inflammatory marker C-reactive protein (CRP) is also linked with CVD outcomes and mortality and may play an important role in the pathway between CMV and mortality. We utilized a U.S. nationally representative study to examine whether CMV infection is associated with all-cause and CVD-related mortality. We also assessed whether CRP level mediated or modified these relationships. Methodology/Principal Findings Data come from subjects ≥25 years of age who were tested for CMV and CRP level and were eligible for mortality follow-up on December 31st, 2006 (N = 14153) in the National Health and Nutrition Examination Survey (NHANES) III (1988–1994). Cox proportional hazard models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for all-cause and CVD-related mortality by CMV serostatus. After adjusting for multiple confounders, CMV seropositivity remained statistically significantly associated with all-cause mortality (HR 1.19, 95% CI: 1.01, 1.41). The association between CMV and CVD-related mortality did not achieve statistical significance after confounder adjustment. CRP did not mediate these associations. However, CMV seropositive individuals with high CRP levels showed a 30.1% higher risk for all-cause mortality and 29.5% higher risk for CVD-related mortality compared to CMV seropositive individuals with low CRP levels. Conclusions/Significance CMV was associated with a significant increased risk for all-cause mortality and CMV seropositive subjects who also had high CRP levels were at substantially higher risk for both for all-cause and CVD-related mortality than subjects with low CRP levels. Future work should target the mechanisms by which CMV infection and low-level inflammation interact to yield significant impact on mortality.